Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan dengan Pengungkapan Corporate Social Responsibility Sebagai Pemoderasi - Nila, Luh; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 23 No 3 (2018)DO - 10.24843/EJA.2018.v23.i03.p20, 2018)
The phenomenon that occurs in the mining company is that any mining activity has the potential to directly impact the environment around the location of mining activities, which greatly affects the stakeholder views of the company. The purpose of this study is the influence of profitability variables and firm size to the value companies in mining companies listed on the Indonesia Stock Exchange Year 2014-2016 with the disclosure of corporate social responsibility (CSR) as a moderating variable. The sample is determined through nonprobability method with purposive sampling technique. This research uses multiple regression test and MRA  test. The results of this study indicate that profitability has no effect on firm value, firm size has a positive effect on firm value, CSR disclosure does not moderate the effect of profitability on firm value, and CSR disclosure does not moderate the influence of firm size to firm value.   Keywords: Profitability, Firm Size, Firm Value, Corporate Social Responsibility Disclosure